2019
DOI: 10.1109/tthz.2018.2881930
|View full text |Cite
|
Sign up to set email alerts
|

Beam Scanning of Silicon Lens Antennas Using Integrated Piezomotors at Submillimeter Wavelengths

Abstract: This paper presents a lens antenna that scans the beam using an integrated piezo-motor at submillimeter wave frequencies. The lens antenna is based on the concept presented in [1], a leaky wave waveguide feed in order to achieve wide angle scanning and seamless integration with the receiver. The lens is translated from the origin of the waveguide producing the scanning of the beam over a 50 deg Field of View (FoV) (or about 6.25 beamwidths) with a maximum scanning loss of 1 dB. The lens movement is achieved wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…Refraction is a classical way to change direction of the EM beams and the mechanical scanning method based on lens antennas is commonly used to realize the continuously changeable refraction angles. Alonso‐delPino et al found a way to steer a beam by changing the position of the feed . Figure a shows the schematic of a 550 GHz silicon lens antenna integrated with a leaky‐wave waveguide feed and a piezoelectric motor.…”
Section: Conventional Terahertz Beam Steering Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Refraction is a classical way to change direction of the EM beams and the mechanical scanning method based on lens antennas is commonly used to realize the continuously changeable refraction angles. Alonso‐delPino et al found a way to steer a beam by changing the position of the feed . Figure a shows the schematic of a 550 GHz silicon lens antenna integrated with a leaky‐wave waveguide feed and a piezoelectric motor.…”
Section: Conventional Terahertz Beam Steering Technologiesmentioning
confidence: 99%
“…b) Measured (solid line) and simulated (dashed line) far‐field radiation patterns with different scanned positions for the incident wave frequency of 550 GHz. Reproduced with permission . Copyright 2019, IEEE.…”
Section: Conventional Terahertz Beam Steering Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The silicon lens was micromachined and required a total amount of 13 wafers for the lower gain version (32 dBi). The same authors recently demonstrated beam steering capabilities with a similar design at 550 GHz [12], however, the presented solution requires movement of the lens by external mechanics, which increases the overall complexity, cost, and volume of the system. Frequency scanned antennas have been shown as a good alternative to mechanically scanned systems due to their lower cost, size, and complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon micromachining has been an enabling technology for low-loss waveguide components at sub-THz frequencies [1], [12], [21]- [23]. Some of the advantages of silicon micromachining are the ability to fabricate features down to the micron scale, batch production, better tolerances, and better batch-to-batch uniformity.…”
Section: Introductionmentioning
confidence: 99%